DIAGNOSIS OF STUDENTS PROFESSIONAL FOCUS - Omonturdiyeva Mahliyo Ochilovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article is about diagnosing career-oriented students.